The Role of Dementia and Residential Service Agency Characteristics in the Care Experiences of Maryland Medicaid Home and Community-Based Service Participants and Family and Unpaid Caregivers. (April 2023) - Fabius, Chanee D.; Millar, Roberto; Geil, Erick; Stockwell, Ian; Diehl, Christin; Johnston, Deirdre; Gallo, Joseph J.; Wolff, Jennifer L.
In Maryland, residential service agencies deliver Medicaid Home and Community-Based Services (HCBS) to older adults with disabilities through direct care workers (e.g., personal care aides). Leveraging survey data from residential service agency administrators, linked to interRAI Home Care assessments for 1144 participants, we describe agency characteristics, and participant and family caregiver experiences by participant dementia status. Most (61.7%) participants experienced low social engagement, and roughly 10.0% experienced a hospitalization or emergency room visit within 90 days. Few (14.4%) participants were served by agencies requiring dementia-specific direct care worker training, and most were served by agencies offering supplemental services, or in which direct care workers helped with health information technology (81.2% and 72.8%, respectively). Few caregivers reported negative care experiences. Participants with dementia and those served by agencies with training and support more often reported negative care experiences. Findings lay the foundation for future longitudinal and embedded interventions within Medicaid HCBS.